Detection and interpretation of impossible and improbable Coma Recovery Scale-Revised scores - Chatelle, C (Arch Phys Med Rehabil, 2016)
OBJECTIVES: To determine the frequency with which specific Coma Recovery Scale-Revised (CRS-R) subscale scores co-occur as a means of providing clinicians and researchers with an empirical method of assessing CRS-R data quality. DESIGN: We retrospectively analyzed CRS-R subscale scores in hospital inpatients diagnosed with DoC to identify impossible and improbable subscore combinations as a means of detecting inaccurate and unusual scores. Impossible subscore combinations were based on violations of CRS-R scoring guidelines. To determine improbable subscore combinations, we relied on the Mahalanobis distance which detects outliers within a distribution of scores. Subscore pairs that were not observed at all in the database (i.e., frequency of occurrence = 0%) were also considered improbable. SETTING: Specialized DOC program and University hospital. PARTICIPANTS: 1190 patients diagnosed with DoC (coma= 76, VS= 464, MCS= 586, EMCS= 64; 794 males; mean age= 43±20 years; traumatic etiology= 747; time post injury= 162±568 days). INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURE(S): Impossible and improbable CRS-R subscore combinations. RESULTS: Of the 1190 CRS-R profiles analyzed, 4.7% were excluded because they met scoring criteria for impossible co-occurrence. Among the 1137 remaining profiles, 12.2% (41/336) of possible subscore combinations were classified as improbable. CONCLUSIONS: Clinicians and researchers should take steps to ensure the accuracy of CRS-R scores. To minimize the risk of diagnostic error and erroneous research findings, we have identified 9 impossible and 36 improbable CRS-R subscore combinations. The presence of any one of these subscore combinations should trigger additional data quality review.